1999
DOI: 10.1177/10298649000030s105
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous chorusing and the origins of music

Abstract: The surprising fit between the basic pattern of hominid sociality (inferred from shared features of human and chimpanzee sociality) and one of the models developed to explain the evolution of synchronous chorusing in insects suggests that synchronous chorusing played a role in the late Miocene separation of the hominid ancestors of humans from our common ancestor with the chimpanzee. A detailed evolutionary scenario for this process is presented which implies that the roots of human music extend some five mill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
200
0
7

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(214 citation statements)
references
References 31 publications
7
200
0
7
Order By: Relevance
“…Several lines of evidence lead to the hypothesis that an areferential songlike communication system predated language in human evolutionary history. This hypothesis was first stated clearly by Darwin (1871), and has since been restated or re-discovered by many others (Livingstone, 1973;Marler, 2000;Merker, 2000Merker, , 2002Mithen, 2005;Richman, 1993) often without attribution (e.g., Brown, 2000). Darwin suggested that a primitive song-like communication system represented a precursor of human language that was adaptive ''for the progenitors of man'' and that modern music exists as a sort of behavioural fossil of this past system.…”
Section: Music As Protolanguagementioning
confidence: 93%
See 2 more Smart Citations
“…Several lines of evidence lead to the hypothesis that an areferential songlike communication system predated language in human evolutionary history. This hypothesis was first stated clearly by Darwin (1871), and has since been restated or re-discovered by many others (Livingstone, 1973;Marler, 2000;Merker, 2000Merker, , 2002Mithen, 2005;Richman, 1993) often without attribution (e.g., Brown, 2000). Darwin suggested that a primitive song-like communication system represented a precursor of human language that was adaptive ''for the progenitors of man'' and that modern music exists as a sort of behavioural fossil of this past system.…”
Section: Music As Protolanguagementioning
confidence: 93%
“…Despite a long history of attempts no uncontroversial definition is currently accepted, and in any case ''music'' as a term is both a new one in English, and not shared in various other languages, which may lump ''music'' with ''dance'' or ''celebration'' as a single term (cf. Merker, 2000Merker, , 2002Nettl, 2000). Nonetheless, music in most cultures is easily and unambiguously singled out (from both language, and other vocalizations and activities) by members of that culture (Nettl, 2000).…”
Section: Linguistic Comparisons: Design Features Of Human Musicmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-verbal communication in nonhuman primates may have been the substrate for the development of 'protolinguistic' forms of communication (Bickerton, 2000). Nonhuman primates long distance calls have been often seen in the frame of a larger evolutionary framework, in the perspective of human vocal and musical rhythms (Merker, 1999;Fitch, 2006;Geissmann, 2000). These series of vocal emissions have been indicated as a possible evolutionary precursor of human music (Merker, 2000;Merker & Okanoya, 2007;Merker et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Nonhuman primates long distance calls have been often seen in the frame of a larger evolutionary framework, in the perspective of human vocal and musical rhythms (Merker, 1999;Fitch, 2006;Geissmann, 2000). These series of vocal emissions have been indicated as a possible evolutionary precursor of human music (Merker, 2000;Merker & Okanoya, 2007;Merker et al 2009). Previous research showed that simultaneous calling patterns given by several individuals within a social group are present in various terrestrial animals including wolves (Harrington & Asa, 2003;Mazzetti et al, 2013), coyotes (McCarley, 1975), and jackals (Jaeger et al, 1996), and in few primate species as gibbons (Geissmann, 2000;Merker, 1999) and indris Maretti et al, 2010).…”
Section: Introductionmentioning
confidence: 99%